2012
DOI: 10.1007/s10103-012-1183-3
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser therapy (808 nm) contributes to muscle regeneration and prevents fibrosis in rat tibialis anterior muscle after cryolesion

Abstract: Muscle regeneration is a complex phenomenon, involving replacement of damaged fibers by new muscle fibers. During this process, there is a tendency to form scar tissue or fibrosis by deposition of collagen that could be detrimental to muscle function. New therapies that could regulate fibrosis and favor muscle regeneration would be important for physical therapy. Low-level laser therapy (LLLT) has been studied for clinical treatment of skeletal muscle injuries and disorders, even though the molecular and cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
86
2
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 40 publications
(53 reference statements)
4
86
2
6
Order By: Relevance
“…In a time‐dependent manner, red and NIR therapies are also able to modulate the gene expression of mediators, such as TNF‐ α , 15, 16 IL1‐ β , 17 IL‐6 18 and TGF‐ β16, 19 as well as genes involved in the differentiation of myogenic stem cells, such as MyoD 18, 20 and myogenin 18, 20 during the muscle repair process.…”
Section: Introductionmentioning
confidence: 99%
“…In a time‐dependent manner, red and NIR therapies are also able to modulate the gene expression of mediators, such as TNF‐ α , 15, 16 IL1‐ β , 17 IL‐6 18 and TGF‐ β16, 19 as well as genes involved in the differentiation of myogenic stem cells, such as MyoD 18, 20 and myogenin 18, 20 during the muscle repair process.…”
Section: Introductionmentioning
confidence: 99%
“…Considerando os critérios de inclusão adotados, foram encontrados um total de 30 estudos nas bases de dados consultadas, dos quais quinze (50%) foram realizados em tendão 3,4,6,9,[22][23][24][31][32][33][34][35][36][37][38] , dez (33,33%) em musculos 12,14,[39][40][41][42][43][44][45] , e cinco (16,66%) em osso e/ou articulação 13,25,[46][47][48] Os resultados mais expressivos obtidos com a terapia foram: diminuição da resposta inflamatória mediante redução de células inflamatórias e modulação de mediadores da inflamação (36,66%), e o aumento da síntese de colágeno (13,33%). Alguns dos demais resultados (50,01%) mencionados foram: angiogênese; redução do estresse oxidativo, do colágeno e da fibrose; aumento do tecido de granulação, da remodelação e síntese óssea, assim como da expressão da proteína da diferenciação miogênica (MyoD) e do fator de crescimento endotelial vascular (VEGF).…”
Section: Resultsunclassified
“…Para as afecções musculoesqueléticas são disponibilizados os lasers à base de arseneto de gálio (Ga-As) e hélio-neônio (He-Ne) 6,11 . Também existem estudos utilizando o laser à base de arseneto de gálio associado a alumínio (GaAlAs) [12][13][14] .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Moreover, several experimental studies from our group have observed the potential effects of both LLLT on muscle damage [20][21][22] and LLLT associated with physical training on muscle performance 23,24 in Wistar rats. However, to our knowledge, the associated effects of LLLT and a physical exercise program on muscle repair have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%